2011
DOI: 10.1038/mt.2011.206
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Efficacy, and Systemic Distribution of Naked, Inhaled Short Interfering RNA (siRNA) and Locked Nucleic Acid (LNA) Antisense

Abstract: Antisense oligonucleotides (ASOs) and small interfering RNA (siRNA) promise specific correction of disease-causing gene expression. Therapeutic implementation, however, has been forestalled by poor delivery to the appropriate tissue, cell type, and subcellular compartment. Topical administration is considered to circumvent these issues. The availability of inhalation devices and unmet medical need in lung disease has focused efforts in this tissue. We report the development of a novel cell sorting method for q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 27 publications
9
95
1
1
Order By: Relevance
“…Moreover, promising results were obtained upon inhalation of free siRNA in human clinical trials for the treatment of patients infected with respiratory syncytial virus [36]. However, recent publications have clearly demonstrated the benefit of nanocarriers for siRNA inhalation therapy [9,32,37]. This was confirmed by our work, as the aspiration of free siRNA in the bronchoalveolar lumen of BALB/c mice resulted in negligible siRNA internalization by rAM and hence also failed to elicit a gene silencing effect.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, promising results were obtained upon inhalation of free siRNA in human clinical trials for the treatment of patients infected with respiratory syncytial virus [36]. However, recent publications have clearly demonstrated the benefit of nanocarriers for siRNA inhalation therapy [9,32,37]. This was confirmed by our work, as the aspiration of free siRNA in the bronchoalveolar lumen of BALB/c mice resulted in negligible siRNA internalization by rAM and hence also failed to elicit a gene silencing effect.…”
Section: Discussionsupporting
confidence: 74%
“…For instance, the cell membrane is impermeable for hydrophilic macromolecules like nucleic acids, precluding direct access of siRNA to the intracellular RNAi machinery. Moreover, it has been reported that free siRNA is more rapidly distributed to the systemic circulation upon local pulmonary application, which decreases the siRNA dose in the bronchoalveolar lumen [9]. To avoid systemic exposure and enhance cellular delivery of siRNA to target cells, siRNAs typically require formulation into lipid-or polymer-based drug carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Although transient, partial, and airway-specific delivery of an miR-138 mimic or anti-SIN3A siRNA might be therapeutic, the efficient delivery of siRNA or miR mimics to airway epithelia is inefficient with current technology (49,50). Further advancements in this field will likely lead to new clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, an efficient siRNA delivery vehicle should still overcome the various extra-and intracellular barriers encountered following inhalation therapy [27].…”
Section: Discussionmentioning
confidence: 99%